2022
DOI: 10.1093/plphys/kiac006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and curation of diploid A-genome wheat species

Abstract: A-genome diploid wheats represent the earliest domesticated and cultivated wheat species in the Fertile Crescent and include the donor of the wheat A sub-genome. The A-genome species encompass the cultivated einkorn (Triticum. monococcum L. subsp. monococcum), wild einkorn (T. monococcum L. subsp. aegilopoides (Link) Thell.), and T. urartu. We evaluated the collection of 930 accessions in the Wheat Genetics Resource Center (WGRC) using genotyping-by-sequencing (GBS) and identified 13,860 curated SNPs. Genomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…The mean θπ of R. agastum was 0.0026 and this taxon had the highest degree of intraspecific individual diversity among the three studied Rhododendron taxa. A greater degree of differentiation between the natural race of einkorn (β) and the hybrid domesticated variety has been observed, with an F ST value between the β race and domesticated einkorn reaching 0.31 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean θπ of R. agastum was 0.0026 and this taxon had the highest degree of intraspecific individual diversity among the three studied Rhododendron taxa. A greater degree of differentiation between the natural race of einkorn (β) and the hybrid domesticated variety has been observed, with an F ST value between the β race and domesticated einkorn reaching 0.31 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present core set will serve as a rich source of genetic variations to be utilized in the breeding program and should be coupled with careful phenotyping. In recent years, gene bank curation has been done to explore the novel genetic variations in T. monococcum [73] , T. aestivum [74] , [75] , [76] , [77] , Aegilops tauschii [43] , T. turgidum L. [78] , rye [79] , sorghum [80] , melon [81] , pumpkin [82] , capsicum [83] for trait improvement.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…It circumscribed to cultivate as wild einkorn. With the introduction of large-scale genomics analysis like genotype by sequencing, SNP array revealed that the origin of T. urartu is the closest genome for subgenome A ( Maccaferri et al, 2019 ; Adhikari L. et al, 2022 ). Furthermore, with the commencement of remarkable genetic diversity losses in the pericentromeric and donating B genome by T. speltoides give a new tetraploid T. turgidum .…”
Section: The Wealth Of Indian Wheat Genetic Resources and Its Conserv...mentioning
confidence: 99%
“…Based on the ex situ germplasm collection size conserved in long-term storage, the Indian National Genebank has the second-largest collection in the world (a total of 459,885 accessions conserved in NGB, India, as on 31 March 2022), next only to the USDA Genebank ( Tyagi et al, 2015 ). In the case of wheat, its ex situ collection in the National Genebank (34,000 accessions as on 31 March 2022) is the fifth-largest collection in the world (CIMMYT Genebank ranks first) ( Jacob et al, 2015 ; Adhikari L. et al, 2022 ). These indigenous germplasm accessions are a valuable repository of economically important traits.…”
Section: Introductionmentioning
confidence: 99%